Management of severe haemolytic anaemia due to residual small mitral paravalvular leak post-percutaneous closure: a case report - Abuelatta, Reda (Eur Heart J Case Rep, 2020)
BACKGROUND: Haemolytic anaemia is a complication of paravalvular leak (PVL). The correlation between the size of the leak and the severity of haemolysis is unclear. Small leaks can cause severe haemolysis, whereas significant leaks may cause no haemolysis. CASE SUMMARY: We report the case of a 40-year-old male who underwent mechanical mitral and aortic valve replacement 20 years ago. In the last 3 years, the procedure was repeated three times due to infective endocarditis. He presented with severe shortness of breath. A transoesophageal echocardiogram with three-dimensional surgical view showed that both discs of the mechanical mitral valve opened sufficiently but a severe PVL had occurred at the 9–12 o’clock position. The location of the mitral valve was abnormal, the sewing ring was inserted high at the mid-interatrial septum. The mechanical aortic valve functioned well. Closure of the transcutaneous PVL was accomplished with two percutaneously implanted devices, leaving a small leak in between. After closure, he developed haemolytic anaemia (haemoglobin: 6 g/dL, lactate dehydrogenase: 1896 units/L, reticulocyte count: 4.6%). He then received 16 units of packed red blood cells. He developed acute kidney injury and was started on haemodialysis. We then installed two additional devices to completely close the mild residual leak and another device to resolve the bidirectional transseptal defect. After 2 days, his renal function returned to normal and anaemia improved (haemoglobin: 9.1 g/dL). DISCUSSION: Mild residual paravalvular leak can cause severe haemolytic anaemia that is correctable via percutaneous closure of the leak.